Pengaruh Nilai Tukar, Inflasi, Produk Domestik Bruto terhadap Ekspor Karet Indonesia Periode 2015 sampai dengan 2022 - Pantalo, Stevin Martha Moia; Saputera, Denny (SAFE-Network, 2024)
This study aims to analyze the influence of exchange rate, inflation rate, and Gross Domestic Product (GDP) growth on Indonesian rubber exports during the period of 2015-2022. The objective of this research is to understand the dynamics of economic factors affecting Indonesian rubber exports and their potential contribution to the national economy. A quantitative research method was employed, utilizing regression analysis to test hypotheses regarding the relationship between the aforementioned variables. Data were obtained from official sources such as Bank Indonesia and the Indonesian Central Statistics Agency (BPS), encompassing exchange rates, inflation rates, GDP, and rubber export data. The analysis indicates that the exchange rate does not significantly influence Indonesian rubber exports. However, the inflation rate exhibits a significant positive impact on rubber export volume, while GDP growth shows a positive but insignificant influence. Simultaneously, exchange rates, inflation rates, and GDP collectively demonstrate a significant impact on rubber exports. This study underscores the importance of considering the economic factors examined in designing policies and strategies to enhance rubber exports in Indonesia. With a deeper understanding of these factors, it is hoped that better guidance can be provided for economic development in the rubber sector and, consequently, for the national economy.